CHILD MARRIAGE PREVENTION BASED ON INTEGRATED PLAN OF POLICY AND ACTION TO REDUCE THE INDEX OF CASE AND PRACTICE OF CHILD MARRIAGE IN REMOTE AREAS - Hanafi, Yusuf (2016)
Child marriage contributes to many dark sides, such as preventing the improvement of human resource and increasing the poverty index. Strategic and collective efforts are needed in order to prevent the existence of this phenomenon, for instance, through organizing a plan of policy and action integratedly. This article aims to portray the social profile of Maduranese people living in South Malang and their tendency towards the practice of child marriage as a need analysis to organize the plan of policy and action prototype to prevent the existence of this dangerous practice. The chosen strategy is solving the child marriage practice in whole area through "circular formula" which relate to law, politic, education, social and religion, and economy area.